Mite “Massudilalong Sola Lebonna” dalam Tradisi Lisan Toraja - nfn mustafa (Balai Bahasa Provinsi Riau, 2020)
AbstractThis paper aims to examine the relevance of Massudilalong Sola Lebonna myth and the life of Torajan community. Massudilalong Sola Lebonna is one of Torajan oral literature forms which is still believed to this day by Torajan community. It serves as an adhesive tool for interpersonal relations and sources of laws and regulations that could open hearts and minds of the people and encourage them to be honest, polite and knowledgeable on manners and custom in their social life. In this study, a structural approach is used. The method and technique used in this study are descriptive namely to expose just what it is. Data were collected by means of note taking techniques, interviews, recording and literature study. The result of the research shows that the myth of Massudilalong Sola Lebonna is highly relevant to the life Torajan community. It is reflected from local wisdoms contained in the myth of Massudilalong Sola Lebonna that becomes basic foundation of interpersonal relationship in Torajan community. The local wisdoms are high self-esteem, firmness, resilience, strong belief and obedience to principles. AbstrakTulisan ini bertujuan untuk mengkaji relevansi mitos dalam Massudilalong Sola Lebonna dengan kehidupan masyarakat Toraja. Massudilalong Sola Lebonna ialah salah satu bentuk sastra lisan Toraja yang hingga kini sebagian besar masih dihayati dan dipercaya oleh masyarakat Toraja. Sastra lisan ini berfungsi sebagai alat perekat hubungan antarindividu dan sumber hukum dan peraturan yang mampu mengetuk hati dan pikiran, serta mengajarkan orang untuk berlaku jujur, berperilaku sopan santun, tahu adat istiadat, dan tata krama dalam hidup bermasyarakat. Pendekatan yang digunakan dalam kajian ini ialah pendekatan struktural. Metode dan teknik yang digunakan dalam kajian ini ialah metode deskriptif, yaitu memaparkan sebagaimana adanya. Pengumpulan data menggunakan teknik pencatatan, wawancara, perekaman, dan studi pustaka. Dari hasil penelitian disimpulkan bahwa mite Massudilalong Sola Lebonna mengandung relevansi yang kuat dengan kehidupan masyarakat Toraja. Hal itu terlihat dari kearifan lokal yang termuat dalam mite Massudilalong Sola Lebonna dijadikan sebagai landasan pokok dalam menjalin hubungan antarsesama masyarakat Toraja. Kearifan lokal tersebut ialah kejujuran, keteguhan, tegas, tangguh, setia pada keyakinan, kuat menjaga harga diri, dan taat asas.